Upregulation of HIF1-α via an NF-κB/COX2 pathway confers proliferative dominance of HER2-negative ductal carcinoma in situ cells in response to inflammatory stimuli - Dominika Piasecka (Neoplasia: An International Journal for Oncology Research, 2020)
There are data to suggest that some ductal carcinoma in situ (DCIS) may evolve through an evolutionary bottleneck, where minor clones susceptible to the imposed selective pressure drive disease progression. Here, we tested the hypothesis that an impact of the inflammatory environment on DCIS evolution is HER2-dependent, conferring proliferative dominance of HER2-negative cells. In tissue samples, density of tumour-infiltrating immune cells (TIICs) was associated only with high tumour nuclear grade, but in 9% of predominantly HER2-negative cases, the presence of tumoral foci (‘hot-spots’) of basal-like cells with HIF1-α activity adjacent to the areas of dense stromal infiltration was noted. Results of in vitro analyses further demonstrated that IL-1β and TNF-α as well as macrophage-conditioned medium triggered phosphorylation of NF-κB and subsequent upregulation of COX2 and HIF1-α, exclusively in HER2-negative cells. Treatment with both IL-1β and TNF-α resulted in growth stimulation and inhibition of HER2-negative and HER2-positive cells, respectively. Moreover, ectopic overexpression of HIF1-α rescued HER2-positive cells from the negative effect of IL-1β and TNF-α on cell growth. Our data provide novel insight into the molecular basis of HER2-dependent proliferation of DCIS cells and indicate the NF-κB/COX2 → HIF1-α signalling axis as a dominant mechanism of DCIS evolution induced by inflammatory microenvironment. Presented findings also highlight the clinical significance of heterogeneity of DCIS tumours and suggest that HIF1-α might be considered as a predictive marker of disease progression.